Precision irrigation based on wireless sensor network. Issue 3 (1st May 2014) - Khriji, Sabrine; El Houssaini, Dhouha; Jmal, Mohamed Wassim; Viehweger, Christian; Abid, Mohamed; Kanoun, Olfa
Abstract : The main purpose of this study is to present a complete irrigation solution for the farmer based on wireless sensor network. The challenge is to create an automated irrigation system which can reduce in the same time the water's waste and is cost effective. Different parameters are important to measure in order to calculate the efficient quantity of water needed by plants. In this study, the proposed solution is the use of low‐cost sensor nodes having reduced power consumption able to realise necessary requirements. The system is composed of different types of nodes. Each node consists of a TelosB mote and adequate sensors or actuators. Soil nodes are used to detect the level of moisture and temperature in soil. Weather nodes monitor the climatic changes. Other nodes are connected to actuators which are able to control the opening of the irrigation valve if necessary.